A aproximação de campo médio de Bethe-Peierls - Stein-Barana, Alzira C.M. [UNESP]; Yoshida, Makoto [UNESP]; Líbero, Valter L. (Sociedade Brasileira de Física, 2004)
As aproximações de campo médio de Pierre Weiss e de Bethe-Peierls são implementadas para o modelo de Ising para ferromagnetismo, salientando-se o papel das flutuações espaciais dos momentos magnéticos localizados. Na aproximação de Bethe-Peierls, embora a Hamiltoniana não seja de partículas independentes, nós mostramos uma forma simples de se obter a energia média da rede utilizando a função de correlação spin-spin. Nós também comparamos a correlação de spins primeiros vizinhos calculada em ambas as aproximações com a solução exata para o sistema bidimensional de spins 1/2. Essa comparação deixa clara a supremacia da aproximação Bethe-Peierls sobre a de Pierre Weiss.

The Pierre Weiss and Bethe-Peierls mean-field approximations are implemented for the ferromagnetic Ising model, with emphasis in the spatial fluctuations of the localized magnetic moments. Although in the Bethe-Peierls approximation we do not have a single-particle Hamiltonian, we present a simple way to obtain the mean energy of the lattice using the spin-spin correlation function. We also compare the next-nearest neighbor spin-spin correlation calculated in both mean-field approximations with the exact result for the two-dimensional lattice of 1/2 spin. This comparison shows clearly the supremacy of the Bethe-Peierls method over the Pierre Weiss one.
The Bethe-Peierls mean-field approximation
Keywords: campo médio; Bethe-Peierls; Ising; mean-field; Bethe-Peierls; Ising